2016
DOI: 10.1108/ijhcqa-05-2015-0054
|View full text |Cite
|
Sign up to set email alerts
|

Trans-disciplinary community groups: an initiative for improving healthcare

Abstract: Adopting TCG could enable healthcare managers to ameliorate their services with little or no extra cost, which is especially important in a budget constraint context and the current quality crisis facing UK healthcare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…This style is important since it is the best way to help staff nurses to work effectively to accomplish the organization goals. In congruence with this, a study in the United Kingdom demonstrated the importance of democratic leadership style in enhancing teamwork, which leads to better patient decision-making and confidence in selfadvocacy (Sideras, 2016).…”
Section: Table (5)mentioning
confidence: 74%
“…This style is important since it is the best way to help staff nurses to work effectively to accomplish the organization goals. In congruence with this, a study in the United Kingdom demonstrated the importance of democratic leadership style in enhancing teamwork, which leads to better patient decision-making and confidence in selfadvocacy (Sideras, 2016).…”
Section: Table (5)mentioning
confidence: 74%
“…Consequently, health policy makers should not just recognise the importance of learning and training activities as enablers for TQM implementation, but design these activities to enhance staff knowledge, skills, creativity, and, consequently, the quality of care they provide to patients (Sideras 2015) TQM in healthcare models emphasize the importance of focusing on patients (customers) and their satisfaction with care. However, patients are assumed to be passive receivers of the care (Galazka, 2019;Mosadeghrad 2013a;Talib et al 2011b).…”
Section: Discussionmentioning
confidence: 99%
“…Participation of patients in community groups, an example of an organisational structure to achieve this, proved successful in enhancing patients' satisfaction and quality of care (Sideras 2015).…”
Section: Discussionmentioning
confidence: 99%